A novel strategy to fabricate high-strength mullite by the reaction sintering method using Al3+/Ce4+-doped SiO2. Issue 9 (1st May 2021) - Zhu, Xianzhong; Chen, Liugang; Zhao, Fei; Gao, Jinxing; Li, Keke; Liu, Xinhong; Xu, Enxia; Ge, Tiezhu; Yang, Liyuan
Abstract: This study presents a novel strategy for fabricating high-strength mullite using Al 3+ /Ce 4+ -doped SiO2 and γ-Al2 O3 powders. Doping of Al 3+ /Ce 4+ ions in SiO2 results in the formation of a large amount of low-viscosity liquid phase in a narrow temperature range, which benefited the particle arrangement (closer) and reduced pores formation, thereby accelerating the mullitization rate and promoting the mullite grains growth. At elevated temperatures, almost all-SiO2 liquid phase were consumed due to a relatively high mullitization rate, and cerianite (CeO2 ) with high melting point gradually precipitated. Thus, the obtained ceramics with highly dense structure, and fully developed elongated columnar slab-shaped mullite grains form an interlocking structure, thereby leading to a high compressive strength (308.0 MPa) and excellent refractoriness under load (1672 °C).